2013
DOI: 10.1086/667362
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Satiation: The Role of Decreasing Desire in Effective Self-Control

Abstract: Self-control is typically viewed as a battle between willpower and desire. The authors focus on the desire side of the equation and extol the positive effect of faster satiation that makes unhealthy behaviors less tempting. They demonstrate that consumers higher in trait self-control demonstrate such "healthy" satiation as they satiate faster on unhealthy foods than on healthy foods. In contrast, those with lower self-control fail to consistently show this differential pattern in their satiation rates. This di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
132
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 42 publications
1
132
1
1
Order By: Relevance
“…Satiation presents a challenge for maintaining happiness because consumers must search for new experiences to maintain the same level of enjoyment (Brickman and Campbell 1971). A remedy could prove instrumental to consumer well-being, and yet previous research has shown few ways to reduce satiation (e.g., Raghunathan and Irwin 2001;Redden 2008). Our research finds a solution by leveraging perceptions of limited availability to establish a new preventive against this phenomenon.…”
mentioning
confidence: 78%
“…Satiation presents a challenge for maintaining happiness because consumers must search for new experiences to maintain the same level of enjoyment (Brickman and Campbell 1971). A remedy could prove instrumental to consumer well-being, and yet previous research has shown few ways to reduce satiation (e.g., Raghunathan and Irwin 2001;Redden 2008). Our research finds a solution by leveraging perceptions of limited availability to establish a new preventive against this phenomenon.…”
mentioning
confidence: 78%
“…So, for example, young children's liking for vegetables can be increased simply by exposing them to pictures of those vegetables (e.g., in books; Houston-Price, Burton, et al, 2009;Houston-Price, Butler, & Shiba, 2009). Intriguingly, visual exposure to food images can also induce satiety: Similar to the gradual reduction of hunger that is seen during actual consumption (Redden & Haws, 2013), even just the simulation of consumption can reduce hunger (Morewedge, Huh, & Vosgerau, 2010). Morewedge et al demonstrated that the mere act of imagining eating a large number of M&M's (vs. a small number) significantly reduced people's subsequent consumption of these candies.…”
Section: Using Visual Images To Encourage Healthy Eatingmentioning
confidence: 99%
“…Self-control is often characterized as a response to psychological conflict between desire (indulge now) versus willpower (delay for health) (Hoch and Lowenstein 1991). Multiple theoretical perspectives have been adopted, with some researchers primarily focused on desire (Redden and Haws 2013) and others on willpower (Hung and Labroo 2011). Effective self-control is thought to depend on: (1) having clear goals,…”
Section: ___________________mentioning
confidence: 99%
“…Consumer studies of traits related to adults' food choices can assist here. For example, adults higher in self-control satiate faster on unhealthy foods than healthy foods (Redden and Haws 2013), and a chronic prevention focus abets selfcontrol through the use of mental budgets when faced with temptation (Krishnamurathy and Prokopec 2010). Although poor self-control occurs across domains (e.g., food and spending, Faber et al 1995), adults who think about the consequences of their behavior, or 'elaborate on potential outcomes,' can exercise greater self-control (Nenkov, Inman and Hulland 2008).…”
Section: ___________________mentioning
confidence: 99%